Eye‐Tracking‐Based Cognitive Assessment and Memory Decline: Need for Clinically Anchored Endpoints...Katsuhisa M, Teshirogi S, Yamamoto S, et al. Eye‐Tracking‐Based Cognitive Assessment Predicts the Risk of Memory Decline: A Community‐Based Cohort Study. Geriatrics & Gerontology International. 2026;26(3):1-8. - Benito‐León, Julián; Benito‐Rodríguez, Carla María (Geriatrics & Gerontology International, 2026)
This article critically evaluates a community-based cohort study by Katsuhisa et al. that investigated the predictive value of an eye-tracking-based cognitive assessment (ETCA) for two-year memory decline measured by the Rivermead Behavioral Memory Test (RBMT). The critique highlights concerns about the study’s definition of memory decline, potential measurement inconsistencies, and the modest sample size, which may limit the reliability and clinical interpretation of ETCA’s predictive accuracy. It also notes that ETCA reflects a composite cognitive-through-gaze measure rather than a purely oculomotor biomarker, suggesting that its association with memory decline may overlap with conventional cognitive testing. The article recommends further research integrating ETCA with multimodal biomarkers and longer follow-up to determine its utility in predicting clinically meaningful cognitive impairment or neurodegenerative disease.